Design of an IoT-Based Automatic Switching System Using Blynk Software - Gregorius Radithya, Linus; Saputri, Fahmy Rinanda; Hadi Prasetya, Indra (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
Optimizing electrical energy consumption is imperative to preserve ecological balance and conserve finite natural resources. One major contributor to inefficient electrical energy consumption is the indiscriminate use of electronic devices. Lighting systems, for example, fundamental in modern living, are often left on unnecessarily, resulting in substantial energy waste. To address this issue, we've introduced an automatic lighting control system that automates light activation and deactivation based on user-defined schedules, promoting energy efficiency and responsible energy use. The primary objective of our research is to design and deploy a Blynk-controlled IoT-based wireless switch control system that enhances energy efficiency by efficiently managing lighting for example conditions according to user-defined parameters. This approach minimizes energy waste, regulates current supply to lighting fixtures, and encourages responsible electronic device usage. Moreover, the system aligns with government initiatives for sustainable energy use and environmental conservation. This paper delves into the detailed design, development, and practical applications of the IoT-based Blynk-controlled wireless switch control system, emphasizing its technical aspects and underscoring the substantial benefits it offers to users and the environment. Our study represents a significant step towards a more sustainable and energy-efficient future, driven by innovative technology and responsible energy management.